Methods of test for petroleum and its products. Kinematic viscosity. Petroleum products. Transparent and opaque liquids. Determination of kinematic viscosity and calculation of dynamic viscosity Part 71-71-1, (31st March 1995) - British Standards Institution,
No abstract available